2017
DOI: 10.21767/2574-2825.1000018
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Use of Nursing Terminology Classification Among Nursing Students- An Action Study

Abstract: Background: Nursing terminology classification enables us to express nursing knowledge in a manner that can be shared across disciplines and care settings. Nursing educators in Israel are committed to training students toward integrating and promoting the use of nursing terminology. This study will display the process of promoting the use of nursing terminology classification among nursing students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The 30 studies can be divided into four groups: attitudes, intent of behavior, and investigation of various factors related to use (ie, influence of environmental climate, leadership, peer pressure)-15 articles 30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] ; examples of different use + ways of assimilation-8 articles [47][48][49][50][51][52][53][54] ; consequences of use including results and quality-5 articles [55][56][57][58][59] ; and use of technology in nurses' education-methods of study-2 articles. 60,61…”
Section: The Systematic Literature Review Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The 30 studies can be divided into four groups: attitudes, intent of behavior, and investigation of various factors related to use (ie, influence of environmental climate, leadership, peer pressure)-15 articles 30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] ; examples of different use + ways of assimilation-8 articles [47][48][49][50][51][52][53][54] ; consequences of use including results and quality-5 articles [55][56][57][58][59] ; and use of technology in nurses' education-methods of study-2 articles. 60,61…”
Section: The Systematic Literature Review Processmentioning
confidence: 99%
“…Of the 30 studies that were found, two researchers were prominent (Dr Gonen with 12 studies 30,36,[41][42][43][44][45]49,52,[59][60][61] and Prof Barnoy with 9 studies 37,38,40,46,50,53,54,56,58 ).…”
Section: Number Of Researchersmentioning
confidence: 99%